2020
DOI: 10.1080/07357907.2020.1844893
|View full text |Cite
|
Sign up to set email alerts
|

Course of Sars-CoV2 Infection in Patients with Cancer Treated with anti-PD-1: A Case Presentation and Review of the Literature

Abstract: The outbreak of COVID-19 pandemia is a major health worldwide concern. Patients with cancer might have a worse outcome, because of the immunosuppression determined by the tumor itself and anti-cancer treatments, including chemotherapy and radiotherapy. The impact and course of viral infection in patients receiving immunotherapy remains unknown. We report the case of a patient with metastatic melanoma, long responder to anti PD-1 blockade who got infected with Sars CoV-2, recovering without sequelae. A critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 19 publications
0
17
0
3
Order By: Relevance
“…Amidst these, the significance of modifying the host immune system is commonly debated, focusing on the clinical trial of the ICI anti-programmed death-1 (PD-1) blocking antibody and treatment currently utilized in oncology [13] . A study conducted by Laura Pala et al, which illustrated the persistence of anti-PD-1 therapy even after successful remission of underlying cancer, and minimal evidence reported in the literature, shows a preventative effect on COVID-19 and PD-1 blockade in cancer patients with and without chronic disease remission [8] . Future studies are required on the interplay of PD-1/PD-L1 inhibition in patients with cancer and COVID-19.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amidst these, the significance of modifying the host immune system is commonly debated, focusing on the clinical trial of the ICI anti-programmed death-1 (PD-1) blocking antibody and treatment currently utilized in oncology [13] . A study conducted by Laura Pala et al, which illustrated the persistence of anti-PD-1 therapy even after successful remission of underlying cancer, and minimal evidence reported in the literature, shows a preventative effect on COVID-19 and PD-1 blockade in cancer patients with and without chronic disease remission [8] . Future studies are required on the interplay of PD-1/PD-L1 inhibition in patients with cancer and COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Laura Pala et al documented the case of a patient with metastatic melanoma, who had been diagnosed with SARS-CoV-2 and healed without side effects in a long-term response to the anti-PD-1 blockade ( Fig. 1 ) [8] . This study and limited findings endorse the likelihood of continuity of immunotherapy in patients with and without comorbidity-free disease and make a conjecture on the defensive function of PD-1 blockade against COVID-19 [8] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our current knowledge on the reciprocal impact of cancer and COVID-19 is limited and unbalanced with respect to the reported cancer entities. ICI was initially developed in and is routinely used as first-line therapy of skin cancer (e.g., melanoma, Merkel cell carcinoma, cutaneous squamous cell carcinoma); there is now increasing data regarding the outcomes of melanoma patients once ICI therapy and COVID-19 coincide [ 42 , 45 , 46 , 47 , 86 ]. However, the experience in lung cancer, breast cancer, gastrointestinal tumors, bladder cancer, and hematological malignancies are most frequently reported.…”
Section: Discussionmentioning
confidence: 99%
“…Gonzalez-Cao et al [ 46 ] observed that the risk of death in melanoma patients undergoing treatment with ICI does not exceed the global risk of death in this population. Interestingly, Pala et al [ 47 ] recently reported that the incidence of symptomatic COVID-19 infection observed in their cohort of patients with advanced malignant melanoma treated with immunotherapy was meaningfully lower as compared with that reported in the overall population in Italy as well as in patients affected by other solid tumors. Finally, a recent Italian survey on ICI treatment in different cancer types revealed that the frequency of ICI treatment was not drastically reduced during the pandemic [ 48 ].…”
Section: Clinical Outcome Of Ici-treated Cancer Patients With Sarsmentioning
confidence: 93%